2023
DOI: 10.1080/14756366.2023.2189578
|View full text |Cite
|
Sign up to set email alerts
|

Design and biological evaluation of 3-substituted quinazoline-2,4(1 H ,3 H )-dione derivatives as dual c-Met/VEGFR-2-TK inhibitors

Abstract: The dual c-Met/vascular endothelial growth factor receptor 2 (VEGFR-2) TK inhibition is a good strategy to overcome therapeutic resistance to small molecules VEGFR-2 inhibitors. In this study, we designed 3-substituted quinazoline-2,4(1 H ,3 H )-dione derivatives as dual c-Met/VEGFR-2 TK inhibitors. We introduced new synthetic methods for reported derivatives of 3-substituted quinazoline-2,4(1 H ,3 H )-dione … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 54 publications
0
18
0
Order By: Relevance
“…To check the affinity of the newly synthesized bis-pyrazoline derivatives against methicillin-resistant S. aureus (MRSA), a molecular docking study was performed. The minimum binding energy confirmed that the target was successfully docked with the ligand molecules. The obtained data suggested that the studied bis-pyrazoline derivatives were fit docked to the effective site pockets of the host in the range of −13.1 to −12.7 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…To check the affinity of the newly synthesized bis-pyrazoline derivatives against methicillin-resistant S. aureus (MRSA), a molecular docking study was performed. The minimum binding energy confirmed that the target was successfully docked with the ligand molecules. The obtained data suggested that the studied bis-pyrazoline derivatives were fit docked to the effective site pockets of the host in the range of −13.1 to −12.7 kcal/mol.…”
Section: Resultsmentioning
confidence: 99%
“…All newly synthetic derivatives were investigated in vitro for their inhibitory activities against VEGFR-2 as a potential molecular target. The VEGFR-2 Kinase Assay Kit (BPS-Bioscience, #78857, USA) 81 , 82 was used for testing the VEGFR tyrosine kinase activity 83 , 84 . Sorafenib was used as a positive control.…”
Section: Methodsmentioning
confidence: 99%
“…The structure of ellipticine encompasses an indole that is fused with an isoquinoline moiety, endowing it with planar structural characteristics. We performed absorption, distribution, metabolism, and excretion (ADME) prediction of ellipticine via an online service [12] (http://www.swissadme.ch/index.php). The results showed that this alkaloid complies with Lipinski's Rule of Five.…”
Section: Ellipticinementioning
confidence: 99%